2021
DOI: 10.1111/jora.12680
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Needed and Useful during the Transition to Young Adulthood

Abstract: A more complete understanding of the role of social relationships during the transition to young adulthood should include the extent to which adolescents believe that others see them as needed and useful. Two samples of late adolescents (Ns = 237, 298) aged 18 to 25 years completed measures of feeling needed and useful by family and friends. Feeling needed and useful by family and friends did not differ across demographic groups, was associated with greater received support, and predicted psychological well‐be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…In addition, adolescents who feel that they are able to contribute meaningfully and help meet their family's needs may feel motivated to contribute to their family further by pursuing greater educational achievement (e.g., engaging with school, studying, performing well on homework assignments and quizzes), which helps to mitigate academic risk (Armstrong‐Carter & Telzer, 2021; Hardway & Fuligni, 2006). Indeed, prior research has shown that adolescents who believe they should assist their family more strongly value academic achievement (Fuligni, 2001) and when adolescents feel more useful they report greater emotional wellbeing (Fuligni et al., 2021). Adolescents in low‐income homes may feel that their provision of chores is relatively more impactful, and therefore derive more fulfillment from it, which in turn contributes to higher levels of school engagement and grades despite the academic risks typically associated with socioeconomic adversity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adolescents who feel that they are able to contribute meaningfully and help meet their family's needs may feel motivated to contribute to their family further by pursuing greater educational achievement (e.g., engaging with school, studying, performing well on homework assignments and quizzes), which helps to mitigate academic risk (Armstrong‐Carter & Telzer, 2021; Hardway & Fuligni, 2006). Indeed, prior research has shown that adolescents who believe they should assist their family more strongly value academic achievement (Fuligni, 2001) and when adolescents feel more useful they report greater emotional wellbeing (Fuligni et al., 2021). Adolescents in low‐income homes may feel that their provision of chores is relatively more impactful, and therefore derive more fulfillment from it, which in turn contributes to higher levels of school engagement and grades despite the academic risks typically associated with socioeconomic adversity.…”
Section: Discussionmentioning
confidence: 99%
“…Individual characteristics can contribute to the development of socially and civically adaptive citizens. We propose that self-regulation when navigating multiple contexts is a key process that influences and/or explains how individuals, with different opportunities, become engaged contributors to society ( Hofmann et al, 2012 , Robson et al, 2020 ) who feel needed and useful ( Fuligni et al, 2022 ).…”
Section: Behavioral and Neural Pathways Of Self-regulationmentioning
confidence: 99%
“…Becoming a contributing citizen, including feeling needed and useful ( Fuligni et al, 2022 ), emerges from the complex interplay between nature and nurture, where our genetic makeup interacts with internal (e.g., hormone changes) and external (e.g., social experiences) environmental factors that shape brain development and the ability to adapt and thrive in society. Structural Magnetic Resonance Imaging (sMRI) studies have shown that there are continuous changes in brain structure throughout adolescence and into early adulthood.…”
Section: Introduction To Growing Up Together In Society (Guts)mentioning
confidence: 99%
“…A sense of being needed is defined in the present study as the perception of the extent to which one contributes to satisfying the needs of others; it is a sense of indispensability and social worthiness (Le Penne, 2017). Empirically, feeling needed has been found to be positively correlated with perceived meaning in life and negatively correlated with depressive symptoms (Fuligni et al, 2022), and the need to be needed is assumed to be a main motive behind concern and activity devoted to contributing to others and society (Moieni et al, 2020). Similarly, feelings of usefulness to others have been shown to go hand in hand with psychological and social well‐being (Gruenewald et al, 2007).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%